Neuroendocrine pathways in alcohol use disorder: opportunities to develop biomarkers for alcohol craving? - Massimo A. Koffler; Lorenzo Leggio (Nutrimentum et Curae)
Recent research developments in the alcohol use disorder (AUD) field have prompted researchers to invest in novel approaches to evaluate alcohol craving. Neuroendocrine pathways portray activity within the central nervous system (CNS) with potential biomarkers that can be collected safely at the peripheral level.